2010
DOI: 10.1002/bit.23021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation yields a highly efficient xylose‐fermenting Zymomonas mobilis strain

Abstract: Zymomonas mobilis is a superb ethanol producer with productivity exceeding yeast strains by several fold. Although metabolic engineering was successfully applied to expand its substrate range to include xylose, xylose fermentation lagged far behind glucose. In addition, xylose fermentation was often incomplete when its initial concentration was higher than 5%. Improvement of xylose fermentation is therefore necessary. In this work, we applied adaptation to improve xylose fermentation in metabolically engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 30 publications
2
47
0
1
Order By: Relevance
“…Agrawall et al [36] also reported that metabolic adaptation was essential for ethanol production by modified strains ofZ. mobilis ZM4 (pZB5).…”
Section: Metabolic Adaptation In Synthetic Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Agrawall et al [36] also reported that metabolic adaptation was essential for ethanol production by modified strains ofZ. mobilis ZM4 (pZB5).…”
Section: Metabolic Adaptation In Synthetic Mediummentioning
confidence: 99%
“…Therefore, although improvements regarding fermentation with this genetically modified Z. mobilis are still needed, the fermentation time and the ability to ferment xylose were both improved. Figure 3 summarizes the metabolic adaptation process insynthetic medium, suggesting that the recombinant Z. mobilis colonies increased ethanol production in the earlier cycles (1-30)but maintained such levels in subsequent cycles (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). This strategy allowed the recombinant to produce ethanol from xylose more efficiently becausehigher participation in ethanol production is derived from this pentose in the latter cycles.…”
Section: Metabolic Adaptation In Synthetic Mediummentioning
confidence: 99%
“…Hence, the discovery of a strain with the capacity to co-utilize all of the sugars derived from biomass is one of the main tasks in cellulosic energy production [38]. Although several genetic and evolutionary engineering approaches achieved efficient pentose utilization in some industrial cell factories, such as those using Zymomonas mobilis [39] and Saccharomyces cerevisiae [40], CCR still remains a major bottleneck. However, it is encouraging that SCUT27/Δldh could consume hexose and pentose almost simultaneously in the SCB hydrolysate, as this could be advantageous in improving productivity and shortening fermentation time in lignocellulosic fuel production.…”
Section: Hydrogen Production From Sugarcane Bagasse Hydrolysatementioning
confidence: 99%
“…(8,(53)(54)(55)(56). Several genetic and evolutionary engineering approaches helped achieve efficient pentose utilization in Z. mobilis and S. cerevisiae (57). Substrate ranges of the above mentioned recombinant strains were also expanded to utilize the disaccharide cellobiose (58)(59)(60).…”
Section: Catabolite Derepression: Molecular Challenge To Lignocellulomentioning
confidence: 99%